The empire of reason : how Europe imagined and Europe realised the enlightenment - Commager, Henry Steele, 1902-1998. (London : Phoenix, 2000)
The foremost American historian of his generation explores America's European origins and shows how the new country embodied the principles of the Enlightenment.
Originally published: London : Weidenfeld & Nicolson, 1978.
Includes bibliographical references and index.
Keywords: Enlightenment -- United States; United States -- Intellectual life -- 18th century; Estados Unidos -- Vida intelectual -- Siglo XVIII